Numerical Simulation and Design Modification of an Automotive Bumper to Enhance Energy Absorption by Using LS-DYNA - Eyob Sisay Yeshanew; Ramesh Babu Nallamothu (Modelling and Simulation in Engineering)
The bumper is a crucial vehicle component designed to protect occupants during front and rear collisions. To maximize fuel efficiency, reducing the total mass of vehicle parts is crucial. The bumper is one of the parts that have slightly more weight. This study was aimed at enhancing the impact resistance of the current bumper design to reduce injuries during vehicular collisions. An evaluation of the existing bumper’s frontal impact was conducted. Following the assessment of the current bumper model, alterations were implemented by modifying its materials and shape and enhancing its thickness. Subsequently, a comparative analysis was performed between the revised design and the original model. CATIA was utilized to create the 3D CAD model of the bumper, and LS-DYNA was then used for finite element analysis utilizing the simulation software. Simulations indicate that the modified bumper’s energy absorption capability surpasses that of existing bumpers made from steel and aluminum alloy by 12.69% and 18.87%, respectively. The impact force of the upgraded aluminum alloy 6061 bumper, which has 4.871 kN, and aluminum alloy 7075 bumper, which has 4.10 kN, is less than that of the current steel bumper, which has 9.78 kN. According to an impact parameter study, the corrugated bumper geometry has a crush force efficiency (CFE) of 81.52%, a total energy absorption (TEA) of 911 J, and a structural energy absorption (SEA) of 148.15 J/Kg. With a SEA of 102.4 J/kg, TEA of 811 J, and CFE of 65.83%, the hollow bumper geometry has lower numbers than these. The deformation slightly increased from 13.5 to 18.1, 20.92, and 23.5 mm, respectively, while the thickness of the improved bumper was altered from 4 to 3.5, 3, and 2.5 mm. However, this does not imply that a thinner bumper is always preferable, and if the deformation gets severe, it might spread into the vehicle’s primary cabin. The von Mises stress, however, rises from 509 to 536, 566, and 592 MPa. It can be said that the optimized model has greatly increased the bumper’s safety and collision resistance without sacrificing the old models’ safety or beauty.